Acesso inteligente: uma porta capaz de aprender - Amorim, Natalia C. de (2018)
Technology has provided effciency and practicity for daily routines of people and companies. The market has solutions to exibilize access that usually uses hard security controls that need cosntant actions from a manager. This way, the paper aims to formalize a control access model that uses artificial intelligence techniques to adapt the users behavior changes and presents a case study of the implementation of this model. It was verified that the model presented satisfactory performance and it is suggested, as future works, the use of neural networks to make a comparison with this work.